Microalbuminuria could improve risk stratification in patients with TIA and minor stroke. Issue 9 (27th July 2016) - Elyas, Salim; Shore, Angela C.; Kingwell, Hayley; Keenan, Samantha; Boxall, Leigh; Stewart, Jane; James, Martin A.; Strain, William David
Abstract: Objective: Transient ischemic attacks (TIA) and minor strokes are important risk factors for recurrent strokes. Current stroke risk prediction scores such as ABCD2, although widely used, lack optimal sensitivity and specificity. Elevated urinary albumin excretion predicts cardiovascular disease, stroke, and mortality. We explored the role of microalbuminuria (using albumin creatinine ratio (ACR)) in predicting recurrence risk in patients with TIA and minor stroke. Methods: Urinary ACR was measured on a spot sample in 150 patients attending a daily stroke clinic with TIA or minor stroke. Patients were followed up at day 7, 30, and 90 to determine recurrent stroke, cardiovascular events, or death. Eligible patients had a carotid ultrasound Doppler investigation. High‐risk patients were defined as those who had an event within 90 days or had >50% internal carotid artery (ICA) stenosis. Results: Fourteen (9.8%) recurrent events were reported by day 90 including two deaths. Fifteen patients had severe ICA stenosis. In total, 26 patients were identified as high risk. These patients had a higher frequency of previous stroke or hypercholesterolemia compared to low‐risk patients ( P  = 0.04). ACR was higher in high‐risk patients (3.4 [95% CI 2.2–5.2] vs. 1.7 [1.5–2.1] mg/mmol, P  = 0.004), independent of age, sex, blood pressure, diabetes, and previous stroke. An ACR greater than 1.5 mg/mmol predicted high‐risk patients (Cox proportional hazard ratio 3.5 (95% CI 1.3–9.5, P  = 0.01). Interpretation: After TIA or minor stroke, a higher ACR predicted recurrent events and significant ICA stenosis. Incorporation of urinary ACR from a spot sample in the acute setting could improve risk stratification in patients with TIA and minor stroke.